(untitled) (Research, Society and Development, 2020)
Objectives: Camellia sinensis has many therapeutic activities and the objectives of this article are to assess the therapeutic properties of C. sinensis through the existing literature, focusing on the activities of greatest interest to Dentistry. Material and methods: Scientific articles published between 2010 and 2020 selected through the BBO, LILACS, Scientific Electronic Library Online (SCIELO) and PubMED platforms were analyzed. 19 articles were relevant to the study. The research method consisted on the use of these following descriptors: "Green tea" "Camellia sinensis", "Properties", "application in Dentistry", "Phytotherapy in dentistry", isolated or together, in portuguese and English. Results: It was seen that Camellia sinensis extract can increase the pH of the dental biofilm and reduce the number of S. mutans in a similar way to chlorhexidine. Of all the articles studied, 15 (65%) did not show an antimicrobial effect of the said plant, 4 of them (20%) showed the antifungal feature and 3 (15%) had positive results on inhibition of erosive attack on the tooth structure, revealing excellent results. Conclusion: The literature points out some of the properties of green tea including its effectiveness as an antimicrobial to pathogenic bacteria and fungi of the mouth, having the potential to be used in clinical practice as a treatment and prevention of oral cavity disorders. Besides that, it was found the need for further deepened studies in more concrete analyzes.